How words mean lexical concepts, cognitive models, and meaning construction - Evans, Vyvyan (Oxford : Oxford University Press, 2009)
'How Words Mean' introduces a new approach to the role of words and other linguistic units in the construction of meaning. It addresses the interaction between non-linguistic concepts and the meanings encoded in language, developing an account of how words are understood when we produce and hear language in situated contexts of use.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Semantics; Cognitive grammar